Effects of tennis play on executive function in 6-11-year-old children: a 12-month longitudinal study - Ishihara, T.; Mizuno, M. (European Journal of Sport Science, 2018)
The present study aimed to assess the effects of 12 months of frequent tennis play on executive functions and the relationships of daily moderate-to-vigorous physical activity (MVPA), physical competence, and enjoyment of playing tennis to executive functions in children. Thirty-two children (6-11 years old) who had regularly played tennis (once a week; mean = 3 years, range = 0-6 years) before the study were enrolled in a 12-month intervention. Participants were allocated into two groups: low-dose (maintain current frequency of tennis play, N = 19) or high-dose (increased frequency of tennis play to four times per week, N = 13). Participants` MVPA, physical competence, enjoyment of playing tennis, and executive functions (i.e. inhibitory control, working memory, and cognitive flexibility) were evaluated before and after this intervention. The high-dose group demonstrated a greater improvement in working memory than the low-dose group, while there was no group difference in MVPA, physical competence, and enjoyment of playing tennis. Changes in MVPA were associated with improvements in cognitive flexibility. Changes in physical competence were associated with improvements in working memory and cognitive flexibility. Changes in the enjoyment of playing tennis were associated with improvements in inhibitory control. The current findings suggest that replacement of MVPA with sports activity, such as tennis enhances executive functions development, and suggest that sports programmes that seek to build competence and enjoyment might help support the development of executive functions in children.